Infrastructure Spending in the Characteristics of the Regions: Towards the Achievement of Sustainable Development Goals - Diana Sulistyowati; Puji Wibowo (The Indonesian Journal of Accounting Research, 2022)
Abstract: Indonesia is faced with challenges by the increasing infrastructure competitiveness globally. In 2019, Indonesia's competitiveness rank declined to 72nd from 141 countries compared to the previous year (World Economic Forum, 2019). Another challenge is also depicted in achieving Sustainable Development Goals (SDGs) 9 dealing with the infrastructure as shown at two indicators that still require special attention. So far, the gaps in infrastructure development still exist in Indonesia after seeing the region's characteristics. The government also supports infrastructure development with a fiscal decentralization system through the Balancing Fund instrument. This study is aimed to analyze the effect of Owned-Source Revenues (OSR) and Balancing Fund Income on infrastructure development in Indonesia by considering infrastructure mandatory spending and aspects of regional characteristics comprise institutional status, geographical conditions, and economic structure. This study uses four-panel data regression modeling and the Generalised Method of Moment (GMM) method for analysis. The results showed that government intervention in mandatory infrastructure spending could moderate the influence of OSR and Balancing Fund income on infrastructure development. In testing based on regional characteristics, the impact of OSR and Specific Grant (Dana Alokasi Khusus/DAK) on infrastructure development is higher. It has a positive value in regions with better financial independence (urban, Java-Sumatra, and metropolitan). Otherwise, the influence of Block Grant (Dana Alokasi Umum/DAU) and Shared Nontax Revenues (Dana Bagi Hasil/DBH) on infrastructure development is stronger. It has a significant positive value in regions with a lower financial independence category (district, non-Java-Sumatra, and non-metropolitan). This research also provides novelty in an analysis of mandatory spending on infrastructure. The central government can use the results of this study to make priorities or maximize the potential of Subnational Governments (SNGs) in infrastructure development, and the ultimate goal is the achievement of the Infrastructure SDGs in Indonesia.Keywords: Infrastructure, Fiscal Decentralization, Regional Characteristics, GMM